Driving Franchisee Success in Indonesia’s F&B MSMEs: The Strategic Role of Entrepreneurial Orientation, Relationship Quality, and Franchisee Innovation - Paski, Heri; Kusumastuti, Ratih Dyah (Jurnal Entrepreneur dan Entrepreneurship, 2025)
Although the franchise business has shown rapid growth, the failure rate in this sector remains relatively high. This condition presents a distinct challenge for franchisors and franchisees in enhancing franchise performance to maintain competitiveness and business sustainability in an increasingly dynamic environment. However, existing studies on franchise performance have predominantly focused on the franchisor's perspective, while giving limited attention to the franchisee's role. This research aims to examine the roles of entrepreneurial orientation (EO), the relationship quality, and innovation in influencing franchisee performance. The research employed a quantitative survey method, collecting data from 70 franchisees in Indonesia's MSME-scale food and beverage (F&B) sector. The data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM–PLS) approach. The results indicate that EO positively affects franchisee performance directly and indirectly through the mediating roles of relationship quality and innovation. While the quality of the franchisor–franchisee relationship significantly enhances performance, its influence on franchisee innovation creation is not statistically significant. In contrast, innovation is a key mediator that transforms EO into performance advantages by generating relevant innovations. This study contributes to the theoretical development of franchise and entrepreneurship by positioning EO as a key strategic driver of franchisee performance, directly and indirectly through relationship quality and franchisee innovation, while contextualizing its relevance in MSME-scale F&B franchises in emerging markets.